Jawetz, Melnick & Adelberg's medical microbiology - Carroll, Karen C; Mietzner, Timothy A.; Hobden, Jeffery A.; Detrick, Barbara; Miller, Steve; Mitchell, Thomas G.; McKerrow, J. H. (James Hobson) 1948-; Morse, Stephen A.; Sakanari, Judy A. (Lange medical book, 2016)
Jawetz, Melnick and Adelbergs Medical Microbiology, introduces you to basic clinical microbiology through the fields of bacteriology, virology, mycology, and parasitology, giving you a thorough yet understandable review of the discipline.